Foremen's intervention to prevent falls and increase safety communication at residential construction sites. Issue 10 (27th June 2016) - Kaskutas, Vicki; Buckner‐Petty, Skye; Dale, Ann Marie; Gaal, John; Evanoff, Bradley A.
Abstract : Background: This research aimed to improve residential construction foremen's communication skills and safety behaviors of their crewmembers when working at heights. Methods: Eighty‐four residential construction foremen participated in the 8‐hr fall prevention and safety communication training. We compared pre‐ and post‐intervention surveys from foremen and their crewmembers to measure the effect of training. Results: Foremen and crewmembers' ratings showed improvements in fall prevention knowledge, behaviors, and safety communication and were sustained 6‐months post‐training, with emphasized areas demonstrating larger increases. Ratings were similar between foremen and crewmembers, suggesting that the foremen effectively taught their crew and assigned accurate ratings. Based upon associations between safety behaviors and reported falls observed in prior research, we would expect a 16.6% decrease in the one year cumulative incidence of self‐reported falls post‐intervention. Conclusions: This intervention improved safety knowledge and behaviors of a large number of workers by training construction foremen in fall prevention and safety communication skills. Am. J. Ind. Med. 59:823–831, 2016. © 2016 Wiley Periodicals, Inc.